2019
DOI: 10.3389/fbioe.2019.00242
|View full text |Cite
|
Sign up to set email alerts
|

In Planta Glycan Engineering and Functional Activities of IgE Antibodies

Abstract: Human immunoglobulin E (IgE) is the most extensively glycosylated antibody isotype so glycans attached to the seven N-glycosites (NGS) in its Fab and Fc domains may modulate its functions. However, targeted modification of glycans in multiply glycosylated proteins remains a challenge. Here, we applied an in vivo approach that allows the manipulation of IgE N-glycans, using a trastuzumab equivalent IgE (HER2-IgE) as a model. Taking advantage of plant inherent features, i.e., synthesis of largely homogeneous com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 41 publications
1
14
0
Order By: Relevance
“…The column was equilibrated with 1.5 CV running buffer (1xPBS, 200 mM NaCl, pH 7.4) before loading the sample. All steps took place at a flow rate of 0.8 mL/min ( Montero-Morales et al, 2019 ). The fractions corresponding to the monomeric peak collected and concentrated with Amicon centrifugal filters, MWCO 10,000 kDa (Merck Millipore).…”
Section: Methodsmentioning
confidence: 99%
“…The column was equilibrated with 1.5 CV running buffer (1xPBS, 200 mM NaCl, pH 7.4) before loading the sample. All steps took place at a flow rate of 0.8 mL/min ( Montero-Morales et al, 2019 ). The fractions corresponding to the monomeric peak collected and concentrated with Amicon centrifugal filters, MWCO 10,000 kDa (Merck Millipore).…”
Section: Methodsmentioning
confidence: 99%
“…While recombinant IgGs are currently most widely used as therapeutic antibodies to combat infections or diseases, alternative antibody formats are gaining attention as potential biopharmaceuticals due to their specific structural properties and binding to different immune receptors (Loos et al, 2014;Brandsma et al, 2019;Montero-Morales et al, 2019). Polymeric antibody formats have a higher valency of antigen-binding sites which has several advantages compared to monomeric antibodies.…”
Section: Introductionmentioning
confidence: 99%
“…These non-human residues are potentially immunogenic and numerous strategies have been employed to prevent their attachment to N-glycans (Montero-Morales and Steinkellner, 2018). These efforts resulted in the formation of human-like N-glycan structures on recombinant glycoproteins including different immunoglobulin classes (Strasser et al, 2008;Loos et al, 2014;Göritzer et al, 2017;Montero-Morales et al, 2019) and showed that plants tolerate extensive engineering of their glycan structures. Different plant expression systems have been used to produce monomeric, dimeric or secretory IgA variants (Ma et al, 1995;Karnoup et al, 2005;Juarez et al, 2013;Virdi et al, 2013;Paul et al, 2014;Westerhof et al, 2014Westerhof et al, , 2015Dicker et al, 2016;Göritzer et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Sialylated therapeutic N-glycoproteins are predominantly produced in eukaryotic expression systems such as plants (Montero-Morales et al, 2019) and mammalian cell lines, particularly Chinese hamster ovary (CHO) cells and human embryonic kidney (HEK) cells, even though these platforms are associated with incomplete glycosylation and low efficiency of sialylation (Thi Sam et al, 2018). Engineering approaches to resolve these limitations have included simultaneous overexpression of human beta-galactoside α-2,6 sialyltransferase I and UDP-GlcNAc 2-epimerase/ManNAc kinase, resulting in yields of sialylated N-glycoprotein increased more than 7-fold compared to the wild-type (Thi Sam et al, 2018).…”
Section: Introductionmentioning
confidence: 99%